Environmental air pollution and chronic rhinosinusitis: A systematic review. Issue 2 (11th March 2022) - Leland, Evelyn M.; Vohra, Varun; Seal, Stella M.; Zhang, Zhenyu; Ramanathan, Murugappan
Abstract: Objective: Chronic rhinosinusitis (CRS) is a highly prevalent and burdensome disease. The pathophysiology is not fully elucidated, but environmental pollutants have been suggested to impact the inflammatory component of the disease process. This review aims to summarize the role of environmental pollution in CRS onset and disease severity. Methods: A systematic review was performed following Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines. PubMed, EMBASE, Cochrane Library, Web of Science, and Scopus databases were queried in August 2021. Original articles reporting on air pollution exposure in CRS were included. Other forms of sinonasal disease were excluded. Results: Literature search produced 11, 983 articles, of which 10 met inclusion criteria. Outcomes evaluated included incidence/prevalence, disease severity, quality of life, and histopathologic/microbial changes. Air pollutant exposure was associated with higher odds of CRS, particularly with particulate matter (PM) exposure. Increasing air pollution exposure was also associated with worsened disease severity and detectable histopathologic changes. Impact on quality of life was less clear. Conclusion: Air pollution (particularly PM) is correlated with CRS incidence/prevalence and disease severity, with evidence of histopathologic changes in CRS tissue samples. Further research is warranted to better understand the mechanisms by which air pollution components may cause CRS and type 2 inflammation. Level of Evidence: 3a Abstract : Recent evidence suggests a role for air pollution in the onset and severity of CRS, most notably with relation to PM2.5 exposure. This systematic review supports previous in vitro and in vivo models of pollution in CRS. This study further adds to the existing body of literature demonstrating the many negative health impacts of exposure to air pollution, including impacts on upper airway disease, lower airway disease, cardiac disease, and overall morbidity and mortality.